Leishmania major surface components and DKK1 signalling via LRP6 promote migration and longevity of neutrophils in the infection site - Ihedioha, Olivia C.; Marcarian, Haley Q.; Sivakoses, Anutr; Beverley, Stephen M.; McMahon-Pratt, Diane; Bothwell, Alfred L. M. (Frontiers in Immunology, 2024)
Background: Host-related factors highly regulate the increased circulation of neutrophils during Leishmania infection. Platelet-derived Dickkopf-1 (DKK1) is established as a high-affinity ligand to LRP6. Recently, we demonstrated that DKK1 upregulates leukocyte-platelet aggregation, infiltration of neutrophils to the draining lymph node and Th2 differentiation during Leishmania infection, suggesting the potential involvement of the DKK1-LRP6 signalling pathway in neutrophil migration in infectious diseases.In this study, we further explored the potential role of DKK1-LRP6 signalling in the migration and longevity of activated neutrophils in the infection site using BALB/c mice with PMNs deficient in LRP6 (LRP6 NKO ) or BALB/c mice deficient in both PMN LRP6 and platelet DKK1 (LRP6 NKO DKK1 PKO ). Relative to the infected wild-type BALB/c mice, reduced neutrophil activation at the infection site of LRP6 NKO or LRP6 NKO DKK1 PKO mice was noted. The neutrophils obtained from either infected LRP6 NKO or LRP6 NKO DKK1 PKO mice additionally showed a high level of apoptosis. Notably, the level of LRP6 expressing neutrophils was elevated in infected BALB/c mice. Relative to infected BALB/c mice, a significant reduction in parasite load was observed in both LRP6 NKO and LRP6 NKO DKK1 PKO infected mice. Notably, DKK1 levels were comparable in the LRP6 NKO and BALB/c mice in response to infection, indicating that PMN activation is the major pathway for DKK1 in promoting parasitemia. Parasite-specific components also play a crucial role in modulating neutrophil circulation in Leishmania disease. Thus, we further determine the contribution of Leishmania membrane components in the migration of neutrophils to the infection site using null mutants deficient in LPG synthesis (Δlpg1 -) or lacking all ether phospholipids (plasmalogens, LPG, and GIPLs) synthesis (Δads1 -). Relative to the WT controls, Δads1 -parasite-infected mice showed a sustained decrease in neutrophils and neutrophilplatelet aggregates (for at least 14 days PI), while neutrophils returned to normal in Δlpg1 -parasiteinfected mice after day 3 PI.Our results suggest that DKK1 signalling and Leishmania pathogen-associated molecular patterns appear to regulate the migration and sustenance of viable activated neutrophils in the infection site resulting in chronic type 2 cell-mediated inflammation.